Academic Resilience as Predictor of Academic Achievement among Secondary School Students - Kaur, Rajwinder; Kaur, Gagandeep (JOURNAL OF INDIAN EDUCATION, 2023)
In the present system of education, understanding of the factors associated to academic achievement is essential and research studies have supported that academic resilience is a major factor influencing the academic achievement. Present study explores the association between these two variables and concluded academic resilience as predictor of the academic achievement with special reference to gender. For this purpose, academic resilience scale developed by Mallick and Kaur was employed on a sample of 488 students studying in Class XI of various schools in Amritsar district of Punjab. The percentage scores of the previous class were taken for academic achievement. Multiple Linear Regression analysis was employed on the total scores as well as on the scores of male and female students. Results revealed that the four dimensions of academic resilience viz. academic confidence, sense of well-being, motivation and ability to get goals, relationship with peers and adults and emotional regulation and physical health are capable of predicting the academic achievement of students.